Komunikasi Organisasi Kunci Meningkatkan Kesehatan Mental Di Pondok Pesantren Nurul Abror Al Robbaniyyin - Abdul Majid; Achmad Faizal Ababil (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2025)
The purpose of this study is because students, Islamic boarding school students, or pupils are vulnerable to stress because they have to face the transition period of living away from parents, maintaining high academic achievement, and adapting to a new environment. This study discusses organizational communication at the Nurul Abror Al-Robbaniyyin Alasbuluh Islamic Boarding School and the research uses a qualitative approach with a case study method. Primary data was obtained through interviews and observations, while secondary data comes from documentation. The subjects in this study were: organizational leaders, organizational members, and students who were not members of organizations at the Nurul Abror Al-Robbaniyyin Alasbuluh Islamic Boarding School. Based on the results of research at the Nurul Abror Al Robbaniyyin Islamic Boarding School (PPNAA), it was found that success and achievement in this institution would not be realized if it was only carried out by a Leader without the help of staff who support every policy and program implemented. The implementation carried out at school is with small things such as greeting each other, no teasing, mutual respect, and helping each other. Organizational communication is an important key in improving mental health, especially at the Nurul Abror Al Robbaniyyin Islamic Boarding School. Effective communication between leaders, structure, and staff, as well as all elements of Al Munaa (Members of the Nurul Abror Al Robbaniyyin Consultative Council) creates an emotionally and psychologically supportive environment.